1224 Sociodemographic and Neonatal Factors Associated with Early Childhood Social-Communication Difficulties in Children Born Preterm. (October 2012) - Wong, HS; Huertas-Ceballos, A; Cowan, FM; Modi, N
Abstract : Background: The Quantitative Checklist for Autism in Toddlers (Q-CHAT) is a parent-completed questionnaire providing a quantitative measure of early childhood social-communication difficulty (Allison et al, J Autism Dev Disord, 2008). The Q-CHAT scores of children born preterm are higher than the general population, indicating greater autistic traits (Wong et al, Neonatal Society Proceedings 2012 Spring Meeting). Aim: To examine sociodemographic and neonatal factors associated with social-communication abilities in preterm infants at 24 months corrected age. Methods: The parents of children born at < 30 weeks gestation and enrolled in a study evaluating routinely collected neurodevelopmental data were asked to complete the Q-CHAT. Children with severe neurosensory disabilities and cerebral palsy were excluded. The effect of factors identified a priori (maternal age, gestation, birthweight z-score, gender, multiple pregnancy, length of mechanical ventilation, supplemental oxygen requirement at 36 weeks post-menstrual age (BPD) and index of multiple deprivation (IMD)) on Q-CHAT scores were examined using univariable and multivariable linear regressions. Results: The Q-CHAT was completed by the parents of 104 children (mean[SD] gestation 27.0[1.7] weeks, when the children were at a mean corrected age of 24.7[2.7] months). On univariable analysis, gestation, multiple pregnancy, BPD and IMD were positively associated with Q-CHAT scores. Low gestation ( p =0.02) and higher IMD ( p <0.01) were independently associated with higher Q-CHAT scores on multivariable analysis. Conclusion: Preterm birth is a recognised risk factor for autism spectrum disorder. We report a novel finding of high deprivation as an independent predictor of early childhood social-communication difficulty in the preterm population.